Kajian Peningkatan Sumber Daya Manusia Bidang Pemasaran Batik Jambi (Studi Kasus: Pengrajin Batik Jambi CV. Kreasi Batik Asmah) - Hario Tamtomo; Wella Sandria (J-MAS (Jurnal Manajemen dan Sains), 2021)
The uniqueness of Jambi Batik can be seen from the type of batik patterned with Arabic calligraphy and fabric edges that adopted Chinese culture. To encourage the success of the batik business in Jambi, entrepreneurs must manage their human resources. This study aims to determine the management of human resources at CV. Kreasi Asmah Batik, located across the city of Jambi. This study uses a qualitative method with a SWOT analysis (Strengths, Weaknesses, Threats and Opportunities). The results showed that: 1) The factors that became the strength of CV. Batik Kreasi Asmah are good quality products, good batik techniques, specialization of unique motifs that are its own uniqueness. 2) Factors that can be used as opportunities for CV. Batik Kreasi Asmah are the increasing purchasing power and interest in batik products. 3) The most threatening factor in CV. Batik Kreasi Asmah are the increasing number of similar businesses with large capital originating from outside the province of Jambi and even produced in Java and resold in Jambi. 4) CV. Batik Kreasi Asmah are in a stable position in the attractiveness of the middle market and middle class market competition.